Assessing the association and predictability of heavy metals in avian organs, feathers, and bones using crowdsourced samples. (August 2020) - Mukhtar, Hussnain; Chan, Chieh-Yu; Lin, Yu-Pin; Lin, Chiao-Ming
Abstract: Birds are bioindicators for research on the relationship between environmental heavy metal concentration levels and accumulation levels in bird tissues. We use roadkill samples, collected by citizen science participants, to investigate the accumulation levels and associations of seven heavy metals in internal organs (heart, liver, and kidney), feathers (primary and breast), and bones (sternum and femur) of two focal species, Amaurornis phoenicurus and Gallinula chloropus. We found that heavy metal accumulation varied by target tissue, and that variables are associated with bird species and heavy metal type. Although Zn and Cu were highest by concentration among both species, Cu was mostly accumulated in internal organs, As in feathers, and Pb in bones. Concentrations of As, Ni, and Pb in feathers of both focal species were lower than those reported in literature, whereas Cd and Cr were above toxic levels. The results also showed that spatial correlation for heavy metal concentration among bird tissues were weaker than non-spatial correlation, suggesting low spatial autocorrelations and variability. In addition, multiple regression analysis revealed significant correlation for Cr, As, and Pb estimations in A. phoenicurus heart, sternum, and kidney, respectively; and potentially Cr in G. chloropus femur by using feathers. These results support the feasibility of using feathers as indicators of As, Cr, and Pb heavy metal contamination to enhance our understanding of heavy metal accumulation in birds, although caution is required for feather-based estimations of Cd, Cu, and Ni concentration. Graphical abstract: Image 1 Highlights: Seven trace metals were assessed in avian internal organs, feathers and bones. Heavy metal accumulation pattern varies among avian tissues and species. As were mostly accumulated in feathers, Pb in bones, and Cd and Cu in internal organs. Feathers showed good predictability of As, Cr and Pb in internal organs and bones. Adult birds are suitable for biomonitoring of heavy metal in environment.